Rohayura Auto Car Wash / Wan Shuhairee Wan Salim... [et al.] - Wan Salim, Wan Shuhairee; Md Saad, Roslee; Ahmad Kamal, Muhammad Fairiz; Samsuri, Mohd Roshidi (2000)
Rohayura Enterprise is a carwash services and maintenance stated in Kangar,Perlis. This company is a partnership company. They started their business on January 2000